2023
DOI: 10.1126/sciadv.adi8534
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 proteomimetic polymers exhibit anti-angiogenic activity in a neovascular age-related macular degeneration mouse model

Wonmin Choi,
Ashley K. Nensel,
Steven Droho
et al.

Abstract: Neovascular age-related macular degeneration (nAMD) is the leading cause of blindness in the developed world. Current therapy includes monthly intraocular injections of anti-VEGF antibodies, which are ineffective in up to one third of patients. Thrombospondin-1 (TSP1) inhibits angiogenesis via CD36 binding, and its down-regulated expression is negatively associated with the onset of nAMD. Here, we describe TSP1 mimetic protein-like polymers (TSP1 PLPs). TSP1 PLPs bind CD36 with high affinity, resist degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated promising therapeutic effects of VEGF-targeted antibody analogs and nanobodies in ophthalmic diseases and cancer. , Nanobodies and antibody mimetics offer advantages over full antibodies, including smaller size, high affinity and specificity, and longer half-life, but they may have limitations, such as immunogenicity, limited target binding sites, and reduced functional complexity. In future research, further exploration of the therapeutic efficacy of nanobodies and antibody mimetics in renal cancer will be conducted to assess their potential in providing more precise and effective targeted treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated promising therapeutic effects of VEGF-targeted antibody analogs and nanobodies in ophthalmic diseases and cancer. , Nanobodies and antibody mimetics offer advantages over full antibodies, including smaller size, high affinity and specificity, and longer half-life, but they may have limitations, such as immunogenicity, limited target binding sites, and reduced functional complexity. In future research, further exploration of the therapeutic efficacy of nanobodies and antibody mimetics in renal cancer will be conducted to assess their potential in providing more precise and effective targeted treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mechanism by which TSCs regulate angiogenesis in tendon healing may involve the modulation of Rap1, TSP1, and VEGF or VEGFR expression. TSP1 is linked to decreased VEGFR expression [ 74 ], whereby it inhibits phosphorylation of VEGFR through CD36 activation, and VEGFR activation is the key to endothelial cell angiogenesis [ 75 ]. In addition, CD36 activation interferes with VEGF-dependent nitric oxide-driven angiogenesis [ 76 ].…”
Section: Discussionmentioning
confidence: 99%